PERUBAHAN FISIK SOSIS DAGING AYAM AFKIR DENGAN PENAMBAHAN ANGKAK SEBAGAI BAHAN KURING - Rumondor, D.; Tinangon, R.; Paath, J.; Tamasoleng, M.; Hadju, R. (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2018)
This study examines the potential of Angkak as a binding compoundin the process of making chicken sausages that are rejected as curingingredients. These physical tests include water binding capacity, pH andcooking losses. The design was carried out in a completely randomizeddesign (CRD) 4 x 4, as a treatment using the angkak level, ie without angkak0%, angkak 0.5%, angkak 1% and angkak 1.5% with replications 4 timesfollowed by BNJ test. The data obtained were analyzed using the SPSSversion 24 program. The results of the diversity analysis showed that therewere significant differences between treatments (P <0.05). This differenceis followed by the BNT test, indicating that the higher the concentration ofAngkak added, the binding capacity of the water will increase (41.38 -42.57). The results of the variance analysis for the pH value of sausages(6.24 - 5.83), showed that there was a significant effect (P <0.05) on thelevel of angkak administration which was then followed by the LSD test.Significant influence also applies to variable cooking losses (P <0.05),cooking shrinkage values 17.74 -12.67. The results of this study can beconcluded that at the level of 0.5% it can affect the physical properties ofwater binding capacity, pH and cooking losses of rejected chicken sausages.Keywords: Sausage, Angkak, Cooking Shrinkage, Water Binding Capacity, pH